Low-Salt Diet Attenuates B-Cell- and Myeloid-Cell-Driven Experimental Arthritides by Affecting Innate as Well as Adaptive Immune Mechanisms - Sehnert, Bettina; Pohle, Sandy; Heuberger, Cornelia; Rzepka, Rita; Seidl, Maximilian; Nimmerjahn, Falk; Chevalier, Nina; Titze, Jens; Voll, Reinhard E. (Frontiers in Immunology, 2021)
A link between high sodium chloride (salt) intake and the development of autoimmune diseases was previously reported. These earlier studies demonstrated exacerbation of experimental autoimmune encephalomyelitis and colitis by excess salt intake associated with Th17- and macrophage-mediated mechanisms. Little is known about the impact of dietary salt intake on experimental arthritides. Here, we investigated if salt restriction can exert beneficial effects on collagen-induced arthritis (CIA) and K/BxN serum transfer-induced arthritis (STIA). CIA depends on both adaptive and innate immunity, while STIA predominantly mimics the innate immune cell-driven effector phase of arthritis. In both models, low salt (LS) diet significantly decreased arthritis severity compared to regular salt (RS) and high salt (HS) diet. We did not observe an aggravation of arthritis with HS diet compared to RS diet. Remarkably, in STIA LS diet was as effective as IL-1 receptor blocking treatment. Complement-fixing anti-CII IgG2a antibodies are associated with inflammatory cell infiltration and cartilage destruction. LS diet reduced anti-CII IgG2a levels in CIA and decreased the anti-CII IgG2a/IgG1 ratios pointing toward a more Th2-like response. Significantly less inflammatory joint infiltrates and cartilage breakdown associated with reduced protein concentrations of IL-1 beta (CIA, STIA), IL-17 (CIA) and the monocyte chemoattractant protein-1 (MCP-1) (CIA) were detected in mice receiving LS diet compared to HS diet. However, we did not find a reduced IL-17A expression in CD4+ T cells upon salt restriction in CIA. Analysis of mRNA transcripts and immunoblots revealed a link between LS diet and inhibition of the p38 MAPK (mitogen-activated protein kinase)/NFAT5 (nuclear factor of activated T-cells 5) signalling axis in STIA. Further experiments indicated a decreased leukodiapedesis under LS conditions. In conclusion, dietary salt restriction ameliorates CIA and STIA indicating at beneficial role of LS diet during both the immunization and effector phase of immune-mediated arthritides by predominantly modulating the humoral immunity and the activation status of myeloid lineage cells. Hence, salt restriction might represent a supportive dietary intervention not only to reduce cardiovascular risk, but also to improve human inflammatory joint diseases like rheumatoid arthritis.